(untitled) (KULT_online, 2019)
To what extend could art be used as a means to politically intervene in the world? Is it possible to consider the effects of art on society as an autonomous art production, instead of discussing its strange and pseudo effect? This anthology Kunst als Alibi comprises Żmijewski’s essays, conversations, and visual conversations, which not only address these questions, but also scrutinize his idea of a practice of ‘Angewandte Gesellschaftskunst’ and its consequences. Edited by Sandra Frimmel, Fabienne Liptay, Dorota Sajewska, and Sylvia Sasse, the authors present various texts that go beyond Żmijewski’s artistic manifesto, his analysis of his own practice, and the analysis of “Kulturinstitutionskultur” (p. 145).